2021
DOI: 10.1108/ebr-11-2020-0288
|View full text |Cite
|
Sign up to set email alerts
|

Pulling from the front or pushing from behind: how competency prioritisation should differ to optimise firm competitiveness

Abstract: Purpose This study aims to contrast the disparities in optimal competitiveness configurations across international economies. Additionally, we analyse the competitive efficiency across firms of different performance endowments to identify distinctions and determine whether standardised or customised competitiveness configurations are optimal. Design/methodology/approach This study uses a multilevel regression model to confirm country-specific effects followed by a non-parametric “Benefit-of-the-Doubt” (BoD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…Lafuente and Vaillant (2021) found that more recent start-ups tend to experience significantly greater competitive efficiency. Also, other trends were found when separating the top-performing firms from the poor performers in each economy.…”
Section: The Entrepreneurship Challenges In Latin America: An Overview Of the Special Issue Manuscriptsmentioning
confidence: 97%
See 4 more Smart Citations
“…Lafuente and Vaillant (2021) found that more recent start-ups tend to experience significantly greater competitive efficiency. Also, other trends were found when separating the top-performing firms from the poor performers in each economy.…”
Section: The Entrepreneurship Challenges In Latin America: An Overview Of the Special Issue Manuscriptsmentioning
confidence: 97%
“…Lafuente and Vaillant (2021) in their paper “Pulling from the front or pushing from behind: how competency prioritisation should differ to optimise firm competitiveness”, recognize that competitiveness is a crucial output of an economy’s entrepreneurial and business activity. Specific competencies, such as innovativeness and technological capabilities, have become requisites for competing in a “Smart” economy.…”
Section: The Entrepreneurship Challenges In Latin America: An Overview Of the Special Issue Manuscriptsmentioning
confidence: 99%
See 3 more Smart Citations